PENGARUH KARAKTERISTIK INDIVIDU, PEMBERDAYAAN DAN KOMUNIKASI INTERNAL TERHADAP KINERJA PEGAWAI ASN DISDUKCAPIL KABUPATEN KEBUMEN - Yogatama Bunadi Putra; Dani Rizana (STISIP Widyapuri Mandiri Sukabumi, 2023)
This study aims to test and analyze whether there is an effect of individual characteristics, empowerment and internal communication on employee performance (a study on the State Civil Apparatus of Disdukcapil, Kebumen Regency). The population in this study were all ASN Department of Population and Civil Registration of Kebumen Regency and sampling technique which is done using saturated sampling technique or the entire population is sampled, namely the State Civil Apparatus (ASN) Disdukcapil Kebumen Regency, amounting to 33 people. The technique of collecting data by distributing questionnaires. The analysis used is validity test, reliability test, classic assumption test, multiple linear regression analysis and the coefficient of determination. The data processing tool used is SPSS for Windows version 25.0. The results of this study indicate that: (1) individual characteristics have a significant influence on the performance of Disdukcapil employees in Kebumen Regency. (2) Empowerment has a significant influence on the performance of Disdukcapil employees of Kebumen Regency. (3) Internal communication has a significant influence on the performance of Disdukcapil employees in Kebumen Regency. (4) Individual Characteristics, Empowerment and Internal Communication together (simultaneously) have a significant and significant influence on the performance of Disdukcapil employees in Kebumen Regency.